Multiple arterial conduits for multi-vessel coronary artery bypass grafting in patients with mild to moderate left ventricular systolic dysfunction: a multicenter retrospective study - Zhang, Hang (J Cardiothorac Surg, 2021)
BACKGROUND: Advantages of multiple arterial conduits for coronary artery bypass grafting (CABG) have been reported previously. We aimed to evaluate the mid-term outcomes of multiple arterial CABG (MABG) among patients with mild to moderate left ventricular systolic dysfunction (LVSD). METHODS: This multicenter study using propensity score matching took place from January 2013 to June 2019 in Jiangsu Province and Shanghai, China, with a mean and maximum follow-up of 3.3 and 6.8 years, respectively. We included patients with mild to moderate LVSD, undergoing primary, isolated multi-vessel CABG with left internal thoracic artery. The in-hospital and mid-term outcomes of MABG versus conventional left internal thoracic artery supplemented by saphenous vein grafts (single arterial CABG) were compared. The primary end points were death from all causes and death from cardiovascular causes. The secondary end points were stroke, myocardial infarction, repeat revascularization, and a composite of all mentioned outcomes, including death from all causes (major adverse events). Sternal wound infection was included with 6 months of follow-up after surgery. RESULTS: 243 and 676 patients were formed in MABG and single arterial CABG cohorts after matching in a 1:3 ratio. In-hospital death was not significantly different (MABG 1.6% versus single arterial CABG 2.2%, p = 0.78). After a mean (±SD) follow-up time of 3.3 ± 1.8 years, MABG was associated with lower rates of major adverse events (HR, 0.64; 95% CI, 0.44–0.94; p = 0.019), myocardial infarction (HR, 0.39; 95% CI, 0.16–0.99; p = 0.045) and repeat revascularization (HR, 0.42; 95% CI, 0.18–0.97; p = 0.034). There was no difference in the rates of death, stroke, and sternal wound infection. CONCLUSIONS: MABG was associated with reduced mid-term rates of major adverse events and cardiovascular events and may be the procedure of choice for patients with mild to moderate LVSD requiring CABG. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1186/s13019-021-01463-5.